(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Cadmium is a confirmed neurotoxicant that causes memory deficits and neuroinflammation through the activation of oxidative stress and inflammatory signalling cascades in the nervous system. 6-Amino Flavone (6-AF): 6-AF is a recently synthesized flavonoid that possesses significant antioxidant and anti-inflammatory effects. This study investigates the protective role of 6-AF against cadmium-induced neurotoxicity in mice. Objectives: To investigate the protective effects of 6-Amino Flavone against cadmium exposure-induced memory impairment and neuroinflammation, as well as to explore its role in modulating the p-JNK/NF-κB signalling pathway. Methods: In total, 250 Swiss albino mice were separated into four groups–control, cadmium, 6-AF treated, and cadmium + 6-AF co-treated groups. Cognitive function was assessed by Morris Water Maze and Y-Maze battery. Oxidative stress markers (MDA, SOD, GSH) were measured by biochemical assay, and inflammatory cytokines (TNF-α, IL-1β, IL-6) and protein expression levels of p-JNK, NF-κB, and IκB-α were quantified using ELISA and Western blot. ANOVA and regression modelling were used to analyze data. Results: Cadmium exposure greatly reduced memory performance and increased oxidative and inflammatory markers. Treatment with 6-AF mitigated these neuroinflammatory effects, improving behavioural outcomes while restoring antioxidant enzyme activity and lowering pro-inflammatory cytokine levels. The regression analysis showed that both MWM and GSH levels were significant predictors of cognition. Molecular data confirmed that p-JNK and NF-κB pathways were downregulated in the 6-AF treated groups. Conclusion: 6-Amino Flavone protects cadmium neurotoxicity reaction through the antioxidant defence and p-JNK/NF-κB mediated anti-inflammatory responses. These results indicate that 6-AF may be a potential therapeutic for neurodegeneration occurring in response to environmental heavy metals.